Bacteriology and tear protein profiles of the dry eye. Issue 2 (February 1986) - Seal, D V; McGill, J I; Mackie, I A; Liakos, G M; Jacobs, P; Goulding, N J
Abstract : The concentrations of tear lysozyme, lactoferrin, ceruloplasmin, IgA, and IgG have been estimated in patients with dry eyes at the same time as semiquantitative bacterial culture was performed of the conjunctivae and lids. Staphylococcal isolations were quantified and biotyped. There was no increased conjunctival colonisation by any particular biotype of Staphylococcus aureus or Staph. epidermidis, and similar numbers of conjunctivae were sterile as in controls (33%); neither were any pathogens such as pneumococci or haemophili isolated. We consider that the conjunctiva of the dry eye, without the lacrimal secretion components of lysozyme and lactoferrin, has an alternative protective antibacterial mechanism which is derived from serum proteins via chronically inflamed vessels.